PENGARUH PENGHINDARAN PAJAK TERHADAP CASH HOLDING PERUSAHAAN DENGAN LEVERAGE DAN RETURN ON ASSET (ROA) SEBAGAI VARIABEL MODERASI - Dessy Natalia Tambunan; Aditya Septiani (Diponegoro Journal of Accounting, 2017)
This study aims to obtain empirical evidence and analyze the effect of tax avoidance on the company's cash holding, as well as the effect of leverage and ROA can moderate the tax avoidance of the cash holding companies.The population in this study is a manufacturing company listed on the Indonesia Stock Exchange Period 2013-2015. The samples selected for use in this study are 223 companie sample that meet the criteria of the sample. The data of this research are analyzed by using descriptive analysis, classical assumption test, hypothesis test with simple linear regression test and multiple linear regression test.The result of this research analysis shows that tax avoidance has a significant negative effect to the company's cash holding, leverage has a significant negative effect in moderating the effect of tax avoidance on the company's cash holding, and Return On Assets (ROA) has a significant negative effect in moderating the effect of tax avoidance on cash holding company.